Study protocol for a parallel-group randomized controlled trial of internet-delivered behavior therapy for adults with Tourette syndrome - Sannemalm, Max; Lybert, Nathalie; Gunnarsson, Lisa; Andrén, Per ; 0000-0003-1358-0166; Kraepelien, Martin; Bragesjö, Maria; Fondberg, Robin; Ivanov, Volen Z; Mataix-Cols, David; Fernández de la Cruz, Lorena; Andersson, Erik; Rück, Christian; et al. (Frontiers in Digital Health, 2025)
INTRODUCTION: Tourette syndrome (TS) and chronic motor or vocal tic disorder (CTD) are neurodevelopmental disorders associated with functional impairment and reduced quality of life. Behavioral therapy (BT) is an effective treatment, but lack of experienced practitioners makes it hard for patients to receive appropriate help. One approach to bridge the gap between demand and availability is to offer the treatment remotely over the internet with minimal support from a therapist. METHODS: This single-blind randomized controlled superiority trial including 110 participants will compare internet-delivered BT (I-BT) primarily consisting of exposure and response prevention (ERP) to a control condition consisting of internet-delivered general psychological support. The primary aim of the trial is to evaluate whether ERP-based I-BT is superior to the control condition in reducing TS/CTD symptoms. The primary outcome measure is the Yale Global Tic Severity Scale - Total Tic Severity score administered by blinded raters at primary endpoint 11 weeks after the treatment start. Secondary endpoints occur at week 23 and 14 months after the treatment start, and the secondary outcomes include tic-related impairment, rates of responders, self-rated tic severity, symptoms of depression, quality of life and cost-effectiveness. Data on dropout rates and adverse events is also collected. DISCUSSION: This is the first randomized controlled trial to evaluate therapist-guided ERP-based I-BT for adults with TS/CTD. The study has been approved by the Swedish Ethical Review Authority (EPM 2023-06541-01). The hypotheses were pre-registered before the start of the data collection. Results from all analyses will be reported according to the Consolidated Standards of Reporting Trials statement for non-pharmacological trials (CONSORT) and Consolidated Health Economic Evaluation Reporting Standards (CHEERS). The participants in the control condition will have the opportunity to receive I-BT after the data from the first follow-up is collected. The study will be published in open access and the results will be shared with service user organizations. At the moment of submission, the study has recruited 87 out of 110 planned participants and the recruitment is expected to be completed in February 2025. TRIAL REGISTRATION: Open Science Framework: https://osf.io/cq97b/ (uploaded 31/01/2024); Clinicaltrials.gov: NCT06271083 (submitted 14/02/2024).
© 2025 Sannemalm, Lybert, Gunnarsson, Andrén, Kraepelien, Bragesjö, Fondberg, Ivanov, Mataix-Cols, Fernández de la Cruz, Andersson, Rück and Ivanova.